Procedure for Submission of Motor Vehicle Insurance Claims at PT. Askrida Syariah Insurance Medan Branch - Adisty Anggraini; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
Askrida Insurance as a company engaged in risk insurance and loss in the future will face fairly stiff competition with other insurance companies, Therefore, in order to survive and be able to compete with other asurnsi companies, there must be more prominent innovations to compete both in terms of product types, prices and intended segments so as to produce products that are able to compete and win competition. From the above explanation, this final task raises the title